FAKTOR FAKTOR YANG MEMPENGARUHI KONSERVATISME AKUNTANSI PADA PERUSAHAAN SEKTOR TRANSPORTASI DAN LOGISTIK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Oktavia Nur; Herman Herman (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2024)
Accounting conservatism is a form of prudence carried out by management in disclosing its financial statements. This study aims to determine the effect of financial distress (FD), debt covenant (DAR), company size (UP), and growth opportunity (GO) on accounting conservatism (CONACC) in transportation and logistics sector companies listed on the Indonesia Stock Exchange for the 2017-2022 period both simultaneously and partially. The population in this study is transportation and logistics sector companies listed on the Indonesia Stock Exchange for the 2017-2022 period. The sampling technique uses purposive sampling. This research is a quantitative research using secondary data. The method used in this study is multiple linear regression analysis. The result of this study is that financial distress and company size partially affect negatively and significantly, while debt to assets ratio and growth opportunitiy do not have a positive and insignificant effect on accounting conservatism. While simultaneous financial distress, debt to asset ratio, company size, and growth opportunity have a significant effect on accounting conservatism. Companies are expected to apply accounting conservatism in the preparation of financial statements to ensure accurate and relevant information.